Epidemiology of anaphylaxis and biphasic reaction in Japanese children. Issue 1 (23rd July 2021) - Ikegawa, Kento; Morikawa, Emi; Nigo, Ayako; Hataya, Hiroshi; Akasawa, Akira
Abstract : Aim: Anaphylaxis is common, but can sometimes be fatal. However, data on the epidemiology and characteristics of anaphylaxis are limited. Although 0.9%–14.7% of anaphylactic reactions in children are biphasic, it is unclear what the characteristics of biphasic reaction are and how long patients with this reaction should be observed. The present study aimed to investigate the epidemiology of anaphylaxis and biphasic reactions and identify the characteristics of the latter. Methods: We conducted an observational study of patients who visited the pediatric emergency department (PED) and were hospitalized for anaphylaxis between March 2010 and March 2017. Results: Of the 264, 689 children who visited our PED, 353 (1.3 per 1, 000 patient) were hospitalized for anaphylaxis, and six (1.7%) had a biphasic reaction. Of the patients with a biphasic reaction, the median time from initial anaphylaxis to the biphasic reaction was 5.9 (interquartile range [IQR] = 3.3–7.6) hours. Symptoms of the initial episode and the biphasic reaction varied. One (0.3%) of the 353 patients developed a clinically important biphasic reaction that required epinephrine administration. Conclusions: The rate of biphasic reactions was 1.7%, and that of clinically important biphasic reactions was 0.3%. Patients with anaphylaxis need to be carefully monitored because of the regular occurrence of biphasic reactions.